Performance of a Novel Hydrophobic Mesoporous Material for High Temperature Catalytic Oxidation of Naphthalene - Guotao Zhao; Zhenxiao Zhao; Junliang Wu; Daiqi Ye (Journal of Spectroscopy)
A high surface area, hydrophobic mesoporous material, MFS, has been successfully synthesized by a hydrothermal synthesis method using a perfluorinated surfactant, SURFLON S-386, as the single template. N2 adsorption and TEM were employed to characterize the pore structure and morphology of MFS. Static water adsorption test indicates that the hydrophobicity of MFS is significantly higher than that of MCM-41. XPS and Py-GC/MS analysis confirmed the existence of perfluoroalkyl groups in MFS which led to its high hydrophobicity. MFS was used as a support for CuO in experiments of catalytic combustion of naphthalene, where it showed a significant advantage over MCM-41 and ZSM-5. SEM was helpful in understanding why CuO-MFS performed so well in the catalytic combustion of naphthalene. Experimental results indicated that MFS was a suitable support for catalytic combustion of large molecular organic compounds, especially for some high temperature catalytic reactions when water vapor was present.